Dramaturgy in Motion : At Work on Dance and Movement Performance - Profeta, Katherine (Book collections on Project MUSE., 2015)
This groundbreaking book moves beyond the conventional association of dramaturgy with plays to consider the substance and process of dramaturgy for dance and movement performance.